Effects of S‐1‐propenylcysteine, a sulfur compound in aged garlic extract, on blood pressure and peripheral circulation in spontaneously hypertensive rats. (30th January 2018) - Ushijima, Mitsuyasu; Takashima, Miyuki; Kunimura, Kayo; Kodera, Yukihiro; Morihara, Naoaki; Tamura, Koichi
Abstract: Objectives: This study was designed to investigate the antihypertensive effect of S ‐1‐propenylcysteine, a characteristic sulfur compound in aged garlic extract, using a hypertensive rat model. Methods: The blood pressure and tail blood flow of both spontaneously hypertensive rats and control Wistar Kyoto rats were measured by the tail‐cuff method and the noncontact laser Doppler method, respectively, at various times after single oral administration of a test compound for 24 h. Key findings: Treatment with S ‐1‐propenylcysteine (6.5 mg/kg BW) significantly decreased the systolic blood pressure of spontaneously hypertensive rat approximately 10% at 3 h after administration, and thereafter, the systolic blood pressure gradually returned to the baseline level in 24 h. The effect of S ‐1‐propenylcysteine was dose‐dependent and was maximal at the dose of 6.5 mg/kg BW at 3 h. However, the other compounds such as S ‐allylcysteine and S ‐allylmercaptocysteine in aged garlic extract were ineffective. In addition, S ‐1‐propenylcysteine had no effect on systolic blood pressure of control Wistar Kyoto rats. Furthermore, S ‐1‐propenylcysteine significantly increased the blood flow at 3 h after administration at the dose of 6.5 mg/kg BW. Conclusions: S ‐1‐propenylcysteine is a key constituent of aged garlic extract responsible for its antihypertensive effect, and the effect of S ‐1‐propenylcysteine involves the improvement in peripheral circulation.